A manuscript present: translatio, media, and mediation in early medieval hispanolatin book culture. Issue 1 (2nd January 2022) - Brown, Catherine
ABSTRACT: The culture of our digital age has a wide streak of nostalgia for digits of flesh, blood, and bone. A good present moment, then, for a present of manuscript. The manuscript codex was digital before we were—only, the digits that made it were flesh and blood fingers instead of zeros and ones. The illuminated codices of early medieval Latin Iberia are particularly articulate about their own status as handmade, handwritten objects. This essay studies what they have to offer us as we think about media, mediation, and textual mobility in our "digital" age.